1998
DOI: 10.1139/z98-042
|View full text |Cite
|
Sign up to set email alerts
|

Population density, survival, and rabies in raccoons in an urban national park

Abstract: Density and survival of a raccoon (Procyon lotor) population in Rock Creek Park, an urban national park inWashington, D.C., were estimated using mark–recapture and radio-tracking over an 8-year period following the appearance ofthe mid-Atlantic States (Mid-Atlantic) rabies epizootic. Raccoon density ranged from 333.3 to 66.7/km2 , with an overall parkestimate of 125/km2 . This density places the Rock Creek population within the range of other urban and suburban populationsand is many times greater than raccoon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(73 citation statements)
references
References 50 publications
2
66
1
Order By: Relevance
“…Our results provide multiple lines of evidence that raccoons operate as a synanthropic species in the suburban Baltimore area, even in the urban matrix with reduced woodland habitat. Our density estimates are within the range reported for raccoons in urban areas, which have ranged between 38-125 raccoons/km 2 (Hoffman and Gottschang 1977; Rosatte et al Riley et al 1998;Prange et al 2003). However, these previous estimates are primarily for raccoons associated with urban parks or open spaces.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Our results provide multiple lines of evidence that raccoons operate as a synanthropic species in the suburban Baltimore area, even in the urban matrix with reduced woodland habitat. Our density estimates are within the range reported for raccoons in urban areas, which have ranged between 38-125 raccoons/km 2 (Hoffman and Gottschang 1977; Rosatte et al Riley et al 1998;Prange et al 2003). However, these previous estimates are primarily for raccoons associated with urban parks or open spaces.…”
Section: Discussionsupporting
confidence: 78%
“…Raccoons have been observed readily utilizing anthropogenic resources, such as refuse for food and human structures for dens (Gehrt 2003;Hadidian et al 2010), and population densities reported for urban areas have consistently been high when compared to rural areas (Rosatte et al 1991;Riley et al 1998;Prange et al 2003). Likewise, home ranges are relatively small in size for raccoons in urban areas which, when combined with high population densities, produces an abundance that tends to exceed other mesocarnivores .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in contact rates between raccoons has been linked to higher prevalence of B. procyonis (Gompper and Wright 2005). Raccoons in urban areas often live at very high densities (Riley et al 1998), and male urban raccoons may be less solitary than their rural counterparts (Prange et al 2003), so the higher prevalence we detected in male raccoons may be a result of increased contact rates among urban male raccoons. There was no difference in the prevalence of B. procyonis in female raccoons from suburban/urban versus rural areas in either time period.…”
Section: Logistic Regression Model Negative Binomial Regression Modelmentioning
confidence: 72%
“…Raccoons can live at high densities in urban areas (Riley et al 1998), with population estimates of 37-94 raccoons/ km 2 in an urban area in southern Ontario, Canada (Broadfoot et al 2001). High raccoon density, combined with their close association with humans, has led to concerns about increased risk of pathogen transmission to humans in urban areas.…”
Section: Introductionmentioning
confidence: 99%